Science and education in times of war: current state and prospects for innovative development - IVANOVA, Tetyana (Ways to Improve Construction Efficiency, 2025)
The article explores the current challenges of functioning and transformation of the education and science system in Ukraine under the conditions of full-scale war. The impact of Russian military aggression on the institutional capacity of the educational and scientific sector, access to knowledge, preservation of human capital, and the effectiveness of state policies for support and recovery in this field is analyzed. A significant number of educational and research institutions have been destroyed or damaged, while millions of students have been forced to flee abroad, switch to distance learning, or suspend their education altogether. Simultaneously, scientific institutions and higher education establishments have faced funding cuts, brain drain, and reorientation of research priorities in response to emerging security challenges. Despite the difficult circumstances, science and education remain among the key drivers of socio-economic resilience, national security, and post-war recovery in Ukraine. The article presents an analysis of the dynamics of academic publication output in Ukraine during 2017–2023, revealing a downward trend largely caused by the COVID-19 pandemic and the ongoing war with Russia. The study examines the dynamics of public and local budget expenditures on education, identifying the main reasons for shifts in financial priorities in supporting scientific and educational activities, including funding for research and development, educational programs, and grants. Emphasis is placed on the growing role of alternative funding sources such as international donor aid, philanthropic initiatives, and private sector involvement. An analysis of international experience in implementing innovative approaches to financing education and science highlights the need for increased investment to foster the innovative development of high-tech sectors. The experience of countries with high levels of innovation (e.g., Israel, Sweden, the United States, Belgium) is examined, demonstrating the importance of adapting their models of resource provision and stakeholder cooperation to the Ukrainian context under martial law. Particular attention is given to promising models of financing diversification in Ukraine, including public-private partnerships, the establishment of social investment funds, student loan schemes, and grant-based support for learners and researchers. The article emphasizes that one of the key strategic directions should be the diversification of funding sources and the strengthening of the legal and regulatory framework to ensure transparency, protection of intellectual property, fair competition, and the minimization of corruption risks. The conclusion underscores that intellectual capital – including education, skills, and innovation – forms the foundation of Ukraine’s long-term competitiveness.